Opening the Minds of Upper Secondary School Students for Business Informatics - Carola Schauer, Hanno Schauer (Proceedings of WI2021, 2021)
Graduates of Business Informatics (BI) have excellent job perspectives. The ongoing digital transformation entails the fascinating opportunity for our students to participate in designing future organizations. At the same time, the analysis of statistical data indicates that first-year-student numbers at Germany’s University bachelor programs in BI are relatively low. Personal experience additionally suggests that many first-year-students have no clear idea about BI and their future role in practice. Hence, we assume that already the perception of BI by students at secondary schools is biased by substantial misconceptions. This paper is intended to contribute to the debate on how to raise the awareness of upper secondary school students for BI. Based on an exploratory survey and practical experience through a case study teaching program employed by "school ambassadors", we propose critical success factors for designing initiatives to disseminate a realistic and attractive image of BI and the professional perspectives it enables.